Et godt arbejdsliv: Livsløb, transition og professionsidentitet - Nielsen, Marie Konge (Tidsskrift for Professionsstudier, 2023)
This article deals with how, when, and why one develops an identity as a professional. To be able to develop a professional identity a good working life is a necessary companion. The underlying premise of this assumption is that the professional needs to be able to internalize the identity, i.e., identify with the profession in a community of practice. The article begins with the Danish society’s demographic development and the appearance of the ageing society. This development is related to the concept life course and the importance of transitions. Specific attention is given to the transition from graduation to working life as a professional. The argument is that older and more experienced generations’ significance for the development of a professional identity is of crucially importance for this transition and therefore also for both attraction to and retention in a profession. The case material is based on the nursing profession.